POROGEN EFFECTS ON AEROSOLIZATION PROPERTIES OF FLUCONAZOLE LOADED PLGA LARGE POROUS PARTICLES - ALIPOUR, SHOHREH; SHIROOEE, ATENA; AHMADI, FATEMEH (International Journal of Applied Pharmaceutics, 2020)
Objective: The most common fungal infection, which is usually occurs in immunocompromised patients, is pulmonary cryptococcosis. Fluconazole (FLZ) is a first-generation triazole which is used for the treatment of pulmonary cryptococcal infection during 6-12 mo. A non-invasive and targeted medication delivery to lung is highly desirable due to lower delivered dose and reduced systemic effects. Large Porous Particles (LPPs) have shown lower phagocytic clearance and higher bioavailability compared to non-porous particles of the same size with a remarkable safety profile. Methods: In the present study, the effect of two different porogen agents with different mechanisms on FLZ loaded PLGA LPPs properties were evaluated using design expert software®. These properties included volume diameter, drug loading, encapsulation efficiency, mass median aerodynamic diameter (MAAD), geometric standard deviation (GSD) and fine particle fraction (FPF). Results: All FLZ-loaded PLGA LPPs (FLZ-PLGA LPPs) showed acceptable volume diameter, drug loading and encapsulation efficiency with rapid FLZ release due to macroporous structure. Significant differences in aerosolization properties in which MAAD, GSD and FPF optimized formulation of the optimized formulation were 6.71±0.4 µm, 1.65±0.08 and 33.20±1.7%, respectively. Conclusion: It was suggested that gas foamed preparation technique using ammonium bicarbonate was a better technique to produce FLZ loaded PLGA LPPs with more suitable in vitro respirable properties.